Non-radical PMS activation by the nanohybrid material with periodic confinement of reduced graphene oxide (rGO) and Cu hydroxides - Shahzad, Ajmal; Ali, Jawad; Ifthikar, Jerosha; Aregay, Gebremedhin G.; Zhu, Jingyi; Chen, Zhulei; Chen, Zhuqi (Journal of hazardous materials, 2020)
[Display omitted] •Cu-rGO LDH nanohybrid fabricated by intercalating rGO inside the LDH galleries.•Cu-rGO LDH exhibited higher surface area and electrical conductivity.•Cu-rGO LDH/PMS induced nonradical pathway.•1O2 generated through SO5− owing to electron conduction between PMS and Cu2+. A new strategy was applied by periodic stacking of active sites of Cu and reduced graphene oxide (rGO) in the form of Cu-rGO LDH nanohybrid material. The experimental results revealed that newly prepared Cu-rGO LDH nanohybrid material was extremely reactive in PMS activation as evident from the degradation rate of 0.115 min−1, much higher than Mn-rGO LDH (0.071 min−1), Zn-rGO LDH (0.023 min−1) or other benchmarked material used during the degradation of bisphenol A (BPA). This excellent activity of Cu-rGO LDH nanohybrid was attributed to the better PMS utilization efficiency as compared to the other catalysts. Additionally, the characterization techniques disclosed that the layer by layer arrangement of active sites in the Cu-rGO LDH catalyst promotes interfacial electron mobility owing to the synergistic association between Cu in LDH and interlayered rGO. Based on the in-situ electron paramagnetic resonance spectroscopy (EPR) and chemical scavengers, singlet oxygen (1O2) was unveiled as dominant reactive species for pollutant removal, resulting from the recombination of superoxides (O2−) or reduction of active Cu centers. We believe that this novel Cu-rGO LDH/PMS system will open up a new avenue to design efficient metal-carbon nanohybrid catalysts for the degradation of emerging aquatic pollutants in a real application.